Congenital bronchogenic cyst: From prenatal diagnosis to postnatal management - Chia-Jung Hsieh; Sheng-Yang Huang; Chia-Man Chou; Jenn-Jhy Tseng (Elsevier, 2024)
Objective: Bronchogenic cysts are rare congenital abnormalities, and usually asymptomatic until adulthood. We present a fetus prenatally diagnosed with a bronchogenic cyst, experiencing compression symptoms immediately after birth and underwent thoracoscopic surgery at 14 days old. Case report: A 33-year-old primigravida had a suspicion of fetal tracheal cyst. Prenatal ultrasound scan revealed a cyst near the trachea at 23 weeks' gestation. Fetal MRI defined a cystic lesion in the upper mediastinum, displacing surrounding vessels. A 3,940 g girl was delivered vaginally at 38 weeks' gestation. Shortly after birth, she developed respiratory distress, and imaging revealed a mediastinal cyst compressing the trachea and esophagus. The cyst was successfully removed through video-assisted thoracoscopic surgery at 14 days old, and pathology confirmed it as a bronchogenic cyst. Follow-up images demonstrated well-aerated lungs. At present, this 1-year-old girl develops normally without respiratory symptoms. Conclusion: Early detection in utero, accurate diagnosis, and timely management are crucial for bronchogenic cysts in neonates.